Penangguhan Eksekusi Terhadap Perkaran Kasasi Nomor 517 K/PDT/2022 Karena Adanya Uoaya Peninjauan Kembali Pada Mahkamah Agung Republik Indonesia - Yunimar, Yunimar; Arianti, Mesi (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
Legal remedies for a request for judicial review in principle do not suspend the implementation of the decision. Article 66 paragraph (2) of Law Number 14 of 1985 concerning the Supreme Court states